2008
DOI: 10.1212/01.wnl.0000310982.99438.54
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging correlates of subjective memory deficits in a community population

Abstract: Subjective memory deficit (SMD) was associated with neuroimaging characteristics in the temporal and hippocampal regions, suggesting that SMD may, at least in some cases, represent a realistic appraisal of underlying brain function independent of measured cognition. However, further research is required for volumetric measures and SMD to establish whether the association reflects lifelong structure or neurodegenerative changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
106
1
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(120 citation statements)
references
References 35 publications
10
106
1
3
Order By: Relevance
“…Two studies found an association between WMH and SCF after adjustment for possible confounders in nondemented elderly from the general population. 15,16 The contradicting results might be explained by the different sample or by a lack of statistical power in our study because our sample size was relatively small compared with these studies (n=109 versus n=1779 and n=1049, respectively).…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Two studies found an association between WMH and SCF after adjustment for possible confounders in nondemented elderly from the general population. 15,16 The contradicting results might be explained by the different sample or by a lack of statistical power in our study because our sample size was relatively small compared with these studies (n=109 versus n=1779 and n=1049, respectively).…”
Section: Discussioncontrasting
confidence: 56%
“…14 A possible association between SCF and cSVD-related brain damage, as proposed by previous research, 1,15,16 and objective cognitive impairment has not been examined before in patients with hypertension.…”
mentioning
confidence: 97%
“…44 In community settings, 20% of individuals with SMC are likely to have dementia and 30% MCI. 38 Establishing the presence of SMCs may prove useful as they have been associated with characteristic neuroimaging changes in the temporal and hippocampal regions 45 , and may represent a degree of cognitive impairment that is not currently measurable by objective tests. 46 SMCs may therefore represent a simple and cost-effective way of identifying underlying impairment which would obviate the need for validated tools and trained administration staff.…”
Section: Performance Of Toolsmentioning
confidence: 99%
“…Each subject data set (T1, T2, and proton density) was readily reconstructed and visually checked for major artifacts before being sent to the database repository (Caen) where it was archived for further analyses. As described in a previous publication, 24 we used the so-called optimized voxel-based morphometry protocol to compute gray matter, white matter (WM), and cerebrospinal fluid volumes of each subject. Total intracranial volume was computed as the sum of the gray matter, WM, and cerebrospinal fluid volumes (both ventricular and extracranial cerebrospinal fluid).…”
Section: Baseline Mri Datamentioning
confidence: 99%